2021
DOI: 10.1155/2021/6614885
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Patient-Related Risk Factors, and Outcomes of Postoperative Pneumonia after Cholecystectomy: A Population-Based Cohort Study

Abstract: Background. Cholecystectomy is one of the most common surgical procedures performed worldwide. The objective of this large, population-based cohort study is to explore the risk factors of pneumonia after cholecystectomy in Taiwan. Methods. From the Taiwanese National Health Insurance Research Database, we selected all patients who underwent cholecystectomy by using ICD-9-codes, from January 1, 1998, to December 31, 2016. The patients were separated into two groups based on the presence or absence of postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therefore, comorbidities such as T2DM can influence morbidity and LoS. A study conducted by Teng et at. (2021) found that 1,587 (26.21%) of the patients with cholelithiasis were diagnosed with T2DM and exhibited complications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, comorbidities such as T2DM can influence morbidity and LoS. A study conducted by Teng et at. (2021) found that 1,587 (26.21%) of the patients with cholelithiasis were diagnosed with T2DM and exhibited complications.…”
Section: Introductionmentioning
confidence: 99%
“…(2021) found that 1,587 (26.21%) of the patients with cholelithiasis were diagnosed with T2DM and exhibited complications. However, research on the effect of T2DM on the outcome of cholecystectomy remains limited and contradictive (Teng et al, 2021). In fact, diabetes has caused many negative effects on the crucial processes of wound healing and cellular function (Burgess et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation